PENGIMPLEMENTASIAN MODEL PEMBELAJARAN PjBL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Anggun Dwi Arianti; Rinaldi Yusup (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning motivation of elementary school students caused by teacher-centered learning and the lack of innovation in the use of learning models. This study aims to determine the increase in student learning motivation through the implementation of the Project Based Learning (PjBL) model. The study used a quantitative approach with an experimental method and a pre-experimental design of the one-group pretest-posttest type. The subjects of the study were all third-grade students of Karadenan State Elementary School in the 2025/2026 academic year, totaling 26 students with a saturated sampling technique. Data collection techniques used questionnaires and tests. Data analysis was carried out through descriptive tests, normality tests, paired sample t-tests, and N-Gain tests. The results showed that there was a significant increase in student learning motivation, indicated by an average pretest score of 45.42 increasing to 89.88 in the posttest with a significance value of 0.000 <0.05. The N-Gain value of 81.83% is included in the high category. In addition, students' cognitive learning outcomes also increased from 50.73 to 87.12 with a significance value of 0.000 < 0.05 and an N-Gain of 75.7% in the high category. Thus, the implementation of the Project Based Learning (PjBL) model is effective in improving the motivation and learning outcomes of elementary school students.